Symptom Severity, Disability, and Parental Emotional Availability in Children with Functional Somatic Symptoms: A Cross-Sectional Study in Kerala, India - Appukuttan, Sreedevi P; Balan, Suma; Natrajan, Gitanjali; Pillai, Bhanu V; Jayakumar, C; Bhaskaran, Renjitha (National Journal of Community Medicine, 2025)
Introduction: Functional somatic symptoms (FSS) are persistent physical complaints without identifiable organic or biochemical abnormalities and are common reasons for healthcare seeking among children and adolescents. This study aimed to correlate somatic symptoms with functional disability, parental illness encouragement, and perceived parental emotional availability in children diagnosed with FSS. Methods: This cross-sectional descriptive correlational study was conducted in the Clinical Psychology outpatient department of a tertiary hospital and included 66 consecutive children aged 8–17 years with FSS. Following ethical approval, data were collected through structured interviews using the Children’s Somatic Symptoms Inventory, Functional Disability Inventory, Illness Behaviour Encouragement Scale, and LUM Emotional Availability of Parents scale. Results: The mean age was 11.80 ± 2.16 years, with males forming 51.5%. Low, moderate, and high symptom severity were noted in 45.5%, 42.4%, and 12.1% respectively. Moderate and severe disability were observed in 43.9% and 15.2%. FSS showed a significant positive correlation with functional disability (r=0.487, p<0.001). Parental reinforcement of illness behaviour showed no significant association with somatic symptoms or disability (p>0.05). Emotional availability of both parents correlated negatively with symptom severity and disability, with paternal emotional availability emerging as a significant negative predictor. Conclusion: Enhance parental emotional availability within management.